2009
DOI: 10.1590/s0102-76382009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da N-acetilcisteína no precondicionamento isquêmico: estudo em corações isolados de ratos

Abstract: Efeitos da N-acetilcisteína no precondicionamento isquêmico: estudo em corações isolados de ratosEffects of n-acetylcysteine on ischemic preconditioning. Study in isolated rat hearts Abstract Objective: The aim of this study is to assess if NAcetylcysteine (NAC) changes the Ischemic Preconditioning (IP) in isolated rat hearts using only one cycle of IP.Methods: Heart Rate (HR), Coronary Flow (CF) and Myocardial Contractility (dP/dt) were registered in 30 Wistar rat's hearts. After anesthesia the hearts were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…These results associate the benefits of omeprazole with the results reported by studies addressing myocardial protection with ischemic preconditioning [8,[25][26][27][28]. The pharmacokinetics basis may be related to changes in transmembrane H + /K + gradients, the first markers of myocardial ischemia, responsible for the repolarization expressed in T-wave morphology of the electrocardiogram [29].…”
Section: Discussionsupporting
confidence: 64%
“…These results associate the benefits of omeprazole with the results reported by studies addressing myocardial protection with ischemic preconditioning [8,[25][26][27][28]. The pharmacokinetics basis may be related to changes in transmembrane H + /K + gradients, the first markers of myocardial ischemia, responsible for the repolarization expressed in T-wave morphology of the electrocardiogram [29].…”
Section: Discussionsupporting
confidence: 64%
“…These results associate the benefits of omeprazole with the results reported by studies addressing myocardial protection with ischemic preconditioning [11][12][13][14][15]. The pharmacokinetics basis may GOMES, OM ET AL -Proteção da recuperação funcional do miocárdio pelo omeprazol após isquemia-reperfusão em corações isolados de ratos…”
Section: Discussionunclassified
“…The association of both treatments was unviable, leading to death of all five animals from R-IPC+NAC group, possibly, a collateral effect of an overdose of NAC, which has been associated in other studies with decrease in prothrombin index and anaphylactoid reactions [21]. Therefore, it has been demonstrated that NAC significantly inhibits the protective mechanism of pre-conditioning for organs such as the myocardium [22].…”
mentioning
confidence: 87%